La ciudadanía versus el pueblo: escenificaciones de polarización política en el espacio público mexicano - Estrada Saavedra, Marco Antonio (El Colegio de México A.C., 2024)
In this study, I explore political polarization through ethnographic observation and comparison of two public demonstrations in Mexico City in late 2022, respectively in opposition to and in support of the country’s National Electoral Institute (INE) reform law. Specifically, I examine how polarization was staged in the public sphere by the respective participants, utilizing speeches, narratives, emotions, varied action repertoires, and diverse forms of symbolic protest for collective self-identification and the stigmatization of the political antagonist. I argue that the enactment of polarization results from the convergence of populist logic and social protest. The research draws upon Niklas Luhmann’s theory of social systems, Eva Illouz and Chantal Mouffe’s sociology of emotions, Jan-Werner Müller’s conceptualization of populism, Ernesto Laclau’s theory of populist reason and Andreas Schedler’s concept of political polarization.